2021
DOI: 10.1080/21655979.2021.1948951
|View full text |Cite
|
Sign up to set email alerts
|

Declined expressions of vast mitochondria-related genes represented by CYCS and transcription factor ESRRA in skeletal muscle aging

Abstract: Age-related skeletal muscle deterioration (sarcopenia) has a significant effect on the elderly's health and quality of life, but the molecular and gene regulatory mechanisms remain largely unknown. It is necessary to identify the candidate genes related to skeletal muscle aging and prospective therapeutic targets for effective treatments. The age-line-related genes (ALRGs) and age-line-related transcripts (ALRTs) were investigated using the gene expression profiles of GSE47881 and GSE118825 from the Gene Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Members of FAM protein family (FAM151a, FAM13a, FAM131a, FAM20c), LGI1 and MYLK3 were also significant DEGs in our study (|log 2 FC|>1). Another transcriptome study analyzed the gene expression data files of human and rats from the Gene Expression Omnibus (GEO) database ( 27 ). Results showed that the expression of mitochondria genes involved in mitochondrial electron transport, complex assembly of the respiratory chain, TCA cycle, oxidative phosphorylation and ATP synthesis were down-regulated in skeletal muscle with aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of FAM protein family (FAM151a, FAM13a, FAM131a, FAM20c), LGI1 and MYLK3 were also significant DEGs in our study (|log 2 FC|>1). Another transcriptome study analyzed the gene expression data files of human and rats from the Gene Expression Omnibus (GEO) database ( 27 ). Results showed that the expression of mitochondria genes involved in mitochondrial electron transport, complex assembly of the respiratory chain, TCA cycle, oxidative phosphorylation and ATP synthesis were down-regulated in skeletal muscle with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increasing studies have utilized transcriptome technology to explore the pathogenesis of sarcopenia in recent years. Some muscle mass and function related genes such as AMPK, IGF-1, CASK, MGMT, UCP3, strength related genes Tnnc1, TPM3, and other metabolism related genes have been verified (26)(27)(28)(29)(30). However, we still lack researches on hormone-related sarcopenia on the transcriptome level.…”
mentioning
confidence: 99%
“…Hence, we find that genes overexpressed in skeletal muscle atrophy are also found to be prioritized in other diseases such as cancer, and neurodegenerative diseases. Mitochondria-related gene MRPS21 has been identified here as well, whose declined expression has been found in sarcopenia or age-related skeletal muscle deterioration [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism and thyroid receptor deficiency, which causes skeletal muscle weakness leads to a simultaneous suppression of mitochondrial metabolic genes, transcription factor A, mitochondrial (TFAM), peroxisome proliferator activator receptor co-activator 1 alpha (PGC1) and ERR expression in the muscle [48]. Aging associated sarcopenia and muscle loss has also been shown to corelate with downregulation of mitochondrial genes linked to tricarboxylic acid cycle, electron transport/respiratory chain, oxidative phosphorylation along with ERR [49]. Likewise, skeletal muscle unloading and reloading, which affects muscle function and mass, suppresses or stimulates the expression of ERRs, respectively [50,51].…”
Section: Expression Of Errs In the Skeletal Musclementioning
confidence: 99%